COGNITIVE STRUCTURES VULNERABILITIES: SYSTEMIC DEFICITS AND DEVELOPMENTAL FRICTION IN ADOLESCENT ATTENTIONAL MATRICES (Multidisciplinary Journal of Science and Technology, 2026)
The neurobiological and psychological maturation of the adolescent brain involves radical restructuring of executive functions, specifically sustained and selective attention. The contemporary developmental landscape, heavily saturated with high-frequency digital stimuli, introduces unprecedented friction into this natural cognitive evolution. This quantitative and qualitative diagnostic investigation empirically evaluates the developmental deficits in voluntary attention among adolescent cohorts. Utilizing a stratified psychometric sampling methodology encompassing 845 secondary school students aged 12 to 15, the study measured cognitive endurance, task-switching efficiency, and attentional volume against standardized neurological baselines. Empirical findings indicate a dominant systemic degradation in sustained attention capacities, with 58.4% of the evaluated cohort demonstrating sub-clinical attentional fragmentation directly correlated with hyper-digital engagement. Multivariate regression models isolated the socioeconomic and environmental antecedents driving this cognitive phenomenon, revealing that unregulated digital multitasking optimizes the brain for high-reward, low-effort stimuli, actively suppressing the maturation of the prefrontal cortex networks responsible for deep cognitive focus. The absence of synchronized cognitive endurance training within standard pedagogical frameworks heavily restricts the rehabilitative capacity of the educational system. We propose robust neuro-pedagogical intervention frameworks, including localized cognitive scaffolding protocols, digital fasting windows integrated into school curricula, and structured neuro-feedback mechanisms, to ensure equitable cognitive developmental environments and restore baseline attentional resilience.